Studi perbandingan tingkat return dan risk antara investasi emas dan saham syariah - Said Muhammad Shahib Marbath; Suazhari Suazhari (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2020)
The purpose of this study is to examine the comparison of Return and Risk levels between gold investment and sharia shares. It is a case study at PT ANTAM and the Jakarta Islamic Index (JII) in 2014-2018. Target population is the gold price of PT ANTAM and shares listed on JII that have been listed on the Indonesia Stock Exchange for a period of five years from 2013. There were 28 companies shares that had been listed on the IDX during the time. The data used obtained from the official website of PT ANTAM for and the official website of the Indonesia Stock Exchange and BNI E-Smart 3.12.4 in the sharia stock price data collection 2013-2018. Hypothesis testing is used by conducting an independent sample T-test analysis. This study shows that the return of Islamic stocks is higher than the Return of gold, but not significantly different and the risk of Islamic stocks is higher than the risk of gold and is significantly different.